Effects of physical activity combined with different visual target presentation durations of ciliary-muscle training on visual acuity in children - Zhou, Sheng; Zhang, Meng; Zheng, Wenbin; Yin, Rongbin; Chen, Gang (Frontiers in Public Health, 2023)
This study aimed to identify the effect of different durations of visual target presentation during ciliary muscle training on children's KVA, UDVA, AL, and accommodative facility. Methods: Based on the ciliary muscle regulation mechanism, an intervention program involving ciliary muscle training with different durations of visual target presentation combined with physical education classes was designed. The intervention aimed to determine the effect of different ciliary muscle training sessions on children's visual acuity. A total of 153 children aged 10-11 years from aschool in Suzhou were enrolled as participants in this 32-week intervention study. This study measured the participants' UDVA and KVA before, during , and after the experimental intervention. Results: After 32 weeks of the intervention, the KVA and UDVA of each experimental group were significantly improved (p < 0.05). Axial length increased significantly in all groups (p < 0.05), and there was a low percentage increase in the 1-s and 3-s groups (0.82%). The accommodative facility was significantly improved in all experimental groups, with a higher improvement percentage in the 3-s and 1-s groups (3.01% and 2.61%). After dividing the children in each group according to their visual acuity, the KVA of children in the 1-s group was significantly improved, the UDVA of children with myopia was significantly increased, and the accommodative facility of children with mild and moderate myopia was significantly improved. Moreover, the KVA, UDVA, and This is a provisional file, not the final typeset article accommodative facility of children with mild and moderate myopia in the 3-s group were significantly improved. The KVA of children with emmetropia and the accommodative facility of children with mild and moderate myopia in the 5-s group were also significantly increased.In school physical education classes, the 1-s, 3-s, and 5-s ciliary-muscle regulating exercise could effectively improve the kinetic visual acuity, uncorrected distance visual acuity, and accommodative facility of children aged 10-11 years. Among them, the effects of the 1-s and 3-s durations are better than that of the 5-s duration, as it can reduce the growth rate of AL and achieve better effect among children with mild and moderate myopia.